Legal Protection Against Bullying Victims in Victimology Perspective - Wicaksono, Ferio Arthato (Journal of Creativity Student, 2018)
Bullying still gets less attention. In Indonesia, victims of bullying are not realized by the perpetrators. Victims of bullying can only be silent, resigned and can't fight back. Protection for victims of bullying is still very minimal. This type of research is a normative juridical research. This research uses a juridical-normative research approach, a statutory approach, and a juridical victimization approach. Legal materials use primary, secondary, and tertiary legal materials. Interpretation in this research uses historical interpretation of the provisions of a law and systematic interpretation. The results showed Victimology identified the rights of victims. This view is very important considering that bullying itself is not considered a problem, but is considered a natural act in childhood. From this point of view, of course, the rights of victims of bullying have not been widely realized, even though the impact of this behavior is very real. Law Number 31 of 2014 concerning Witness and Victim Protection cannot be applied effectively to handle victims and assist victims if there is a legal process that occurs because the Witness and Victim Protection Agency exists only at the center, not in the regions. So that the protection of witnesses and victims is only carried out by the relevant agencies and the police.